Peningkatan Kesadaran Gizi Seimbang sebagai upaya Pencegahan Anemia pada Remaja Putri - Nurpadilla Nurpadilla; Fitriani Fitriani; A. Reski Amelia; Dahikatul Jannah; Mila Regina Putri; Sera Sera (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Anemia among adolescent girls is one of the health problems that is often overlooked, even though it has serious impacts on learning concentration, productivity, and reproductive health in the future. One of the main causes of anemia is iron deficiency and an unbalanced diet. This community service activity aims to increase adolescent girls’ knowledge about anemia prevention through health promotion using poster media with the approach of “Smart Nutrition for Iron Health.” The activity was carried out at Pesantren Al-Mubarak 12 November 2025, targeting 34 adolescent girls. The method included planning, preparation, implementation, and evaluation stages, with pre-test and post-test conducted to assess participants’ knowledge levels. The results showed a significant increase in adolescents’ knowledge regarding anemia prevention. Before the activity, 55% of respondents had poor knowledge, 35% moderate, and only 10% good. After the intervention, 75% of respondents had good knowledge and 25% moderate, with no respondents in the poor category. These results indicate that poster media is effective in increasing adolescents’ understanding of anemia and the importance of consuming a balanced diet rich in iron as an effort to prevent anemia among adolescent girls.